2018
DOI: 10.1016/j.ebiom.2018.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Metformin from mother to unborn child – Are there unwarranted effects?

Abstract: For more than 40 years, metformin has been used before and during pregnancy. However, it is important to note that metformin can cross the placenta and circulate in the developing foetus. Recent studies reported that the concentration of metformin in foetal cord blood ranges from half to nearly the same concentration as in the maternal plasma. Since metformin has anti-cell growth and pro-apoptotic effects, there are persistent concerns over the use of metformin in early pregnancy. Current human studies are lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 78 publications
(115 reference statements)
0
52
0
1
Order By: Relevance
“…Metformin coadministration before and during an ART cycle for women with PCOS 36 has been part of protocol in many ART clinics. Recent studies have reported that metformin can be transported to child from mother through placental circulation during pregnancy 37 and that its concentration in fetal cord blood is close to that of maternal blood. Moreover, metformin treatment does not lower the risk of developing gestational diabetes in high-risk women.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin coadministration before and during an ART cycle for women with PCOS 36 has been part of protocol in many ART clinics. Recent studies have reported that metformin can be transported to child from mother through placental circulation during pregnancy 37 and that its concentration in fetal cord blood is close to that of maternal blood. Moreover, metformin treatment does not lower the risk of developing gestational diabetes in high-risk women.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was previously reported that metformin impaired insulin secretion in primary human and mouse islets, and in rat pancreatic beta cell lines in a normoglycemic environment 61,62 , it has been reported that metformin enhanced mouse pancreatic progenitor cells 63 and protected mouse pancreatic beta cells exposed to fatty-acid induced stress 64 and high glucose 65 . Therefore, metformin overuse without metabolic challenge could cause beta cell toxicity 66 but in a hyperglycemic environment, as in this Figure 5: Photomicrograph of the diabetic + glibenclamide (group 5) fetal pancreas using H&E (x100), numerous developing islets Langerhans ( ) with irregular interlobular ducts ( ) slightly less developed than that of the insulin group within the developing pancreatic cells research, metformin is protective to the pancreas. Figure 5 showed numerous developing Islet cells with many irregular interlobular ducts following treatment with glibenclamide.…”
Section: Fetal Pancreasmentioning
confidence: 90%
“…Consequently, many women conceive using metformin, therefore it is essential to ensure it is safe to take in early pregnancy. Metformin has a short half-life and readily crosses the placenta, although the extent of metformin uptake by the embryo and fetus is unclear [28]. This is particularly relevant as there is evidence to suggest that the fetal blood concentrations of metformin, using cord blood sampled at birth, may be greater than the maternal serum concentration of metformin [29].…”
Section: Does Pre-pregnancy or Obstetric Intervention Improve The mentioning
confidence: 99%
“…However, a note of caution for future investigation is raised from in vitro mouse and human fetal testicular tissue cultures, which, when exposed to metformin, have a decrease in testosterone secretion and Sertoli cell number. This, if occurring in vivo, could potentially lead to a significant adverse male reproductive transgenerational effect due to in utero metformin exposure [28,32,33].…”
Section: Does Pre-pregnancy or Obstetric Intervention Improve The mentioning
confidence: 99%